Preventing Persons Affected by Serious Mental Illnesses from Obtaining Firearms: The Evolution of Law, Policy, and Practice in Massachusetts. (4th March 2015) - Silver, James; Fisher, William H.; Silver, Emily
Abstract : A history of commitment to a mental health facility disqualifies applicants for gun licenses. Identifying such a history has become increasingly complex as the locus of confinement has become more diversified and privatized. In Massachusetts, prior to 2014, the databases used to identify individuals who would be disqualified on such grounds had not contemporaneously matched the evolution of the state's mental health systems. A survey of Massachusetts police chiefs, who, as in many jurisdictions, are charged with certifying qualification, indicates that some have broadened the scope of their background checks to include the experience of their officers with respect to certain applicants. The survey identifying these patterns, conducted in 2014, preceded by one month significant legislative reforms that mandate the modification of the reporting into a centralized database commitments to all types of mental health and substance use facilities, thus allowing identification of all commitments occurring in the state. The anticipated utilization of a different database mechanism, which has parallels in several other states, potentially streamlines the background check process, but raises numerous concerns that need to be addressed in developing and using such databases. Copyright © 2015 John Wiley & Sons, Ltd.